1999
DOI: 10.1051/forest:19990609
|View full text |Cite
|
Sign up to set email alerts
|

Relations entre la qualité du liège, sa composition minérale et la composition minérale des feuilles du chêne-liège (Quercus suber L.)

Abstract: -Relationships between the quality of cork, its inorganic content and the inorganic content of the leaves of the corkoak (Quercus suber L.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
7
1
2
Order By: Relevance
“…Although no relationship has been reported in the literature we could access, the study stresses a positive correlation between cork quality and phosphorus, probably due to its role in cellular multiplication and lignification processes (Martin Prevel 1978;Harris et al 1999). We could not support the positive influence of potassium reported by Courtois and Masson (1999), since the variability for this element was limited.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…Although no relationship has been reported in the literature we could access, the study stresses a positive correlation between cork quality and phosphorus, probably due to its role in cellular multiplication and lignification processes (Martin Prevel 1978;Harris et al 1999). We could not support the positive influence of potassium reported by Courtois and Masson (1999), since the variability for this element was limited.…”
Section: Discussioncontrasting
confidence: 50%
“…Dettori et al (1996) found a negative correlation between soil depth and cork quality expressed as a score derived from the sum of 15 physical and mechanical parameters. Courtois and Masson (1999), studying the relationships among cork quality, its mineral composition and the mineral composition of cork oak leaves, found a positive correlation between cork potassium content and cork quality. Elevation, in the data set analysed here, ranged from 120-830 m a.s.l., offering a good representation of cork production areas in Sardinia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several authors, environment influences cork quality (Isasa 1959;Ahmed 1994;Dettori et al 1996;Courtois and Masson 1999;Pizzurro and Maetzke 2009) and the conditions favouring an intense vegetative activity may cause an increase in the diameter of lenticels and a decrease in the commercial value of cork (Natividade 1950).…”
Section: Introductionmentioning
confidence: 98%
“…It is also a forest with a health deficit and high tree density, located in a semiarid climate. In this situation, the decline is affecting the proper functioning of the phellogen, causing an increase in porosity, but not in the already low growth rate (Courtois and Masson, 1999).…”
Section: Discussionmentioning
confidence: 99%